Penetapan kadar flavonoid total dan aktivitas antioksidan ekstrak etanol, fraksi n-heksan, etil asetat daun senggani (Melastoma candidum D.Don) secara spektrofotometri visibel - Apmarja, Sarah Utami; Nasution, Muhammad Amin; Nasution , Haris Munandar; Yuniarti , Rafita (Journal of Pharmaceutical and Sciences, 2025)
Medicinal plants are natural sources that have antioxidant activity, characterized by the content of phenolic and flavonoid components in reducing free radicals which depends on the number of hydroxyl groups in their molecular structure. One of the plants that contain flavonoid compounds which have antioxidant activity is senggani leaves (Melastoma candidum D.Don). This research aimed to determine the chemical compounds contained in the ethanol extract, to determine the total flavonoid value of the ethanol extract, the ethyl acetate fraction and the n-hexane fraction and to determine the antioxidant activity of the ethanol extract, the ethyl acetate fraction and n-hexane fraction. The stages of this research include processing plant materials, making ethanol extract, making ethyl acetate fraction and n-hexane fraction, characterization examination, phytochemical screening, and determining the total flavonoid content of ethanol extract, ethyl acetate fraction and n-hexane fraction of senggani leaves using Visible and Spectrophotometric methods. Determination of the antioxidant activity of ethanol extract, ethyl acetate fraction, and n-hexane fraction using different techniques, namely DPPH with ABTS. The results of phytochemical screening on simplicia powder and ethanol extract contained chemical compound groups such as alkaloids, flavonoids, saponins, tannins, steroids/triterpenoids, and glycosides. The results of determining the total flavonoid content in the ethanol extract of senggani leaves were 44.7805 ± 0.176606439 mgQE/g; In the ethyl acetate fraction, it was 48.421 ± 0 mgQE/g, and in the n-hexane fraction it was 31.491 ± 0.091844121 mgQE/g. The results of antioxidant activity using the DPPH method obtained an IC₅₀ value for the ethanol extract of 12.51 (μg/ml); in the ethyl acetate fraction of 9.42 (μg/ml); in the n-hexane fraction, it was 40.45 (μg/ml), and in the vitamin C standard it was 4.32 (μg/ml). Antioxidant results using the ABTS method obtained an IC₅₀ value for the ethanol extract of 8.21(μg/ml); in the ethyl acetate fraction of 5.93(μg/ml); in the n-hexane fraction, it was 23.35(μg/ml), and in the vitamin C odor it was 2.65(μg/ml).